2016
DOI: 10.1371/journal.pone.0167979
|View full text |Cite
|
Sign up to set email alerts
|

A Low Dose of Dietary Quercetin Fails to Protect against the Development of an Obese Phenotype in Mice

Abstract: The purpose of this study was to examine the effect of a 40% high-fat diet (HFD) supplemented with a dietary attainable level of quercetin (0.02%) on body composition, adipose tissue (AT) inflammation, Non-Alcoholic Fatty-Liver Disease (NAFLD), and metabolic outcomes. Diets were administered for 16 weeks to C57BL/6J mice (n = 10/group) beginning at 4 weeks of age. Body composition and fasting blood glucose, insulin, and total cholesterol concentrations were examined intermittently. AT and liver mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…) and we have previously found JNK phosphorylation to be elevated in the adipose tissue of mice consuming the same HFD utilized in this experiment (Enos et al. , , ; Cranford et al. ).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…) and we have previously found JNK phosphorylation to be elevated in the adipose tissue of mice consuming the same HFD utilized in this experiment (Enos et al. , , ; Cranford et al. ).…”
Section: Resultssupporting
confidence: 63%
“…It should be noted that an attempt was made to examine adipose tissue macrophage infiltration (F4/80 immunohistochemistry) in order to corroborate the qRT‐PCR data as in our previous publications (Enos et al. , , ). However, due to unspecific positive staining as a result of the elevated adipose tissue fibrosis exhibited by the mir155 −/− HFD mice, we were unable to accurately assess macrophage infiltration by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Some studies have shown that dietary quercetin can reduce diet‐induced obesity; others have not . Difference in diets as well as quercetin molecular forms, dosage, and duration of treatment could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%